EFEKTIFITAS PENGGUNAAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA POWER POINT TERHADAP KOMPETENSI BELAJAR SISWA DI KELAS XI MIA SMA NEGERI 1 PADANG BOLAK - adi israyadi lubis; Dedes Asriani Siregar; Lia Purnama Sari (JURNAL PhysEdu (PHYSICS EDUCATION), 2020)
Abstract This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model assisted by power point media on the learning competence of business and energy material students in Class XI MIA. This research was conducted using a quasi-experimental method with two group pretest-posttest design. The population in this study were all students of class XI consisting of 4 classes with a total of 128 students. The sampling technique used was simple random sampling technique, so the sample in this study was class XI MIA1 as an experimental class and class XI MIA2 as a control class totaling 70 students. Based on data analysis obtained: (1) student learning outcomes of business material and energy class XI before the application of Power Point Contextual Teaching and Learning (CTL) models assisted by power point media obtained an average score of 59.02 in the "Less" category; (2) Student learning outcomes of class XI business and energy material after applying the Contextual Teaching and Learning (CTL) Model assisted with power point media obtained an average value of 80.68 which was in the "Good" category. Based on data analysis, it was found that t count was greater than t table (3.31> 1.66). So it can be concluded that "there are significant differences in student learning competencies using the Contextual Teaching and Learning (CTL) model assisted by power point media with student learning competencies using conventional models assisted with power point media in class XI MIA". Keywords: Contextual Teaching and Learning (CTL) models assisted by power point, business and energy media, Physics Learning competencies.